Association Between Family Support and Nurse Motivation in Managing Patients with COVID-19 - Hoda, Ferdinandus Suban; Mahoklory, Serly Sani; Pello, Yakoba Ketzia; Riti, Irlin Falde (IJNP (Indonesian Journal of Nursing Practices), 2021)
Background: Coronavirus (COVID19) is a world public health emergency. The coronavirus transmission is highly fast that health workers are at high risk of contracting COVID-19. It raises excessive anxiety for nurses when caring for COVID-19 patients, so one way to help reduce the fears and worries nurses face is by providing support and motivation from their families.Purpose: This study aims to determine the relationship between family support and nurses’ motivation in caring for Patients with COVID19.Methods: The method used was correlational quantitative, involving 84 nurses caring for Patients with COVID19.Result: The results of the spearman rank test showed a p-value of 0,001 ≤ α 0,05, which indicated a relationship between family support and the motivation of nurses in caring for Patients with COVID19. Furthermore,the coefficient correlation (r = 0,362) had a low level of relationship with a positive direction of the relationship.Conclusion: It can be concluded that family support is very important in the psychological dimension by positively affecting nurses' work motivation